The Journey to Separate but Equal : Madame Decuir's Quest for Racial Justice in the Reconstruction Era - Beermann, Jack M. (Book collections on Project MUSE., 2021)
"[This book] examines the tragic case of Hall v. DeCuir (1878) that helped pave the way for Plessy v. Ferguson's legitimation of the judicial doctrine and social practice of 'separate but equal' facilities. The book tells the story of the injustice done to Madame Josephine DeCuir in July 1872 aboard the Governor Allen steamship on her overnight journey up the Mississippi River from New Orleans to Point Coupee Parish. DeCuir was denied a room in the ladies' cabin due to her status as a woman of color. Nine days after the trip she filed suit against Captain John Benson, claiming that the refusal to accommodate her violated an 1869 Louisiana statute. The Supreme Court case that followed-=, in which the US Supreme Court reversed the Louisiana Supreme Court's decision, is a rich source of information about the racial attitudes in the aftermath of the Civil War, the special situation of the French-speaking people of color in Louisiana, and the post-Reconstruction 'redemption' of the South that followed the disputed election of 1876"--